An antimony(iii) borate with large birefringence exhibiting unwonted [B5O11] fundamental building blocks and dimeric [Sb2O6] clusters. Issue 10 (13th April 2021) - Chen, Zhen; Zeng, Hao; Han, Shujuan; Yang, Zhihua; Pan, Shilie
Abstract : By combining π-conjugated [B3 O6 ] groups and Sb 3+ cations with SCALP, we successfully obtained the second antimony(iii ) borate SbB5 O9 with a large birefringence (0.151 @ 1064 nm), which exhibits unwonted [B5 O11 ] FBBs and dimeric [Sb2 O6 ] clusters. Abstract : A new birefringent crystal SbB5 O9 has been synthesized by combining π-conjugated [B3 O6 ] groups and Sb 3+ cations with SCALP. It exhibits the unwonted [B5 O11 ] fundamental building block (FBB) and dimeric [Sb2 O6 ] cluster. Remarkably, SbB5 O9 exhibits a short UV cutoff edge (below 240 nm) and a large birefringence (Δ n = 0.151 @ 1064 nm) which is even better than that of the well-known commercial birefringent material α-BaB2 O4 (α-BBO) (Δ n = 0.122 @ 532 nm). First-principles calculations show that the birefringence enhancement mainly originates from the highly distorted [Sb2 O6 ] dimer and π-conjugated B–O anionic groups.